2006
DOI: 10.1158/0008-5472.can-05-4590
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expansion of Marginal Zone B Cells in Eμ-API2-MALT1 Mice Is Linked to Enhanced IκB Kinase γ Polyubiquitination

Abstract: The translocation t(11;18)(q21;q21) that generates an API2-MALT1 fusion protein is the most common structural abnormality among the genetic defects reported in mucosaassociated lymphoid tissue (MALT)-type lymphomas, and its presence correlates with the apparent lack of further genetic instability or chromosomal imbalances. Hence, constitutive nuclear factor-KB (NF-KB) activation induced by the API2-MALT1 fusion protein is considered essential for B-cell transformation. To examine its role in B-cell development… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 37 publications
2
57
0
Order By: Relevance
“…Although transient transfection of wild type MALT1 does not significantly activate NF-κB, overexpression of its oncogenic form potently activates NF-κB in vitro [42,45]. Consistent with these results, transgenic mice expressing Eµ-API2-MALT1 have elevated NF-κB activity [46]. On the other hand, genetic inactivation of Malt1 gene in mice impairs TCR-induced NF-κB activation [47,48].…”
Section: Cbm Proteins In Antigen Receptor Signalingmentioning
confidence: 64%
“…Although transient transfection of wild type MALT1 does not significantly activate NF-κB, overexpression of its oncogenic form potently activates NF-κB in vitro [42,45]. Consistent with these results, transgenic mice expressing Eµ-API2-MALT1 have elevated NF-κB activity [46]. On the other hand, genetic inactivation of Malt1 gene in mice impairs TCR-induced NF-κB activation [47,48].…”
Section: Cbm Proteins In Antigen Receptor Signalingmentioning
confidence: 64%
“…In addition to disrupting TRAF2 binding and/or oligomerization, deletions or mutations of the BIR1 domain might also disrupt other vital functions of the API2 moiety of API2-MALT1. For example, a recent report suggested that the BIR1 domain of API2 might contribute to API2-MALT1-dependent NF-kB activation by promoting association of the fusion protein with membrane lipid rafts (Baens et al, 2006). Another recent report demonstrated that the API2 BIR1 interacts with Bcl10 (Hu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, targeting the MALT1 C-terminus to the rafts appeared to be sufficient to activate NF-kB. 55 Likewise, permanent raft association of the fusion protein in splenic lymphocytes from API2-MALT1 transgenic mice and of API2-MALT1-expressing BJAB B cells was associated with increased polyubiquitination of IKKg and NF-kB activity respectively. 55,56 Raft association might facilitate oligomerization of the API2-MALT1 fusion protein and/or the interaction of its MALT1 domains with downstream signaling components like TRAF6, in this way bypassing the normal antigen requirement for formation of MALT1-TRAF6 oligomers and resulting in constitutive NF-kB activation.…”
Section: Pathogenesis Of Malt Lymphomasmentioning
confidence: 99%
“…A role for TRAF6 is supported by the finding that an API2-MALT1 fusion lacking the C-terminal TRAF6 binding site still resided in the lipid rafts, though it was incompetent to activate NF-kB. 55 On the other hand, a recent study questioned a role for TRAF6 in NF-kB activation by API2-MALT1, 51 which warrants further studies.…”
Section: Pathogenesis Of Malt Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation